Bank of Japan Interventions and the Volatility of the Dollar/Yen Exchange Rate - Georgios Chortareas; Ying Jiang (Credit and Capital Markets – Kredit und Kapital, 2017)
We analyse the impact of Bank of Japan"s (BoJ) intervention on the volatility of the USD/JPY exchange rates under a regime switching framework. We find that the Yen intervention decreases the volatility, and the impact is only significant when market volatility is low. – – Die Interventionen der japanischen Zentralbank und die Volatilität des Dollar/Yen-Wechselkurses Der Beitrag analysiert den Effekt von Interventionen der japanischen Notenbank (BoJ) auf die Volatilität des USD/JPY-Wechselkurses im Rahmen eines Regime-Switching Modells. Die Ergebnisse zeigen, dass Interventionen die Volatilität senken. Allerdings ist der Effekt nur dann signifikant, wenn die Marktvolatilität niedrig ist.
Keywords: F31; G15; 330; Foreign Exchange Intervention; Exchange Rate Volatility; Regime Switching GARCH